Review: Cancer Cells Resistance Strategies - Ali Faris Hassan1 , Nada Naji Al-Shawi 1, Mahmood Kahtan Salih1 , Pharmacsit Rusul Mohammed Hassan A (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cancer, which is the most important health problem, develops the ability to resistant traditional medicationsthis leads to increase efforts to develop new cancer medication protocols. In this review, the chemotherapyresistance could be due to several mechanisms. These mechanisms involve either inactivation by twoimportant phases, phase I which involve oxidation, reduction and hydrolysis or phase II which involveconjugation wi, alteration of the target site which decrease either activation of anticancer prodrug and/ordecrease its influx to cancer cells. Other mechanisms for chemotherapy resistance return to the repairingof cancer cell DNA, modulation of efflux for drug, inactivation of apoptosis, besides how the role ofheterogeneity of tumor cells in drug resistance. All of these strategies obligated the oncologist to use acombination of chemotherapy medication to overcome or avoid resistances to treatments.